Healthy Living: Hyperglycemia and Hypoglycemia - Jennifer Hillan; Emily Minton (EDIS, 2011)
If you have diabetes, you may experience low blood glucose levels (hypoglycemia) or high blood glucose levels (hyperglycemia) from time to time. Both can be serious if not treated. Therefore, it’s important to learn about hypoglycemia and hyperglycemia so you can prevent and treat them before they cause health problems. This revised 3-page fact sheet describes the causes, symptoms, treatment, and prevention of each of these conditions. Written by Jennifer Hillan and Emily Minton and published by the UF Department of Family Youth and Community Sciences, March 2011.